2022
DOI: 10.3390/brainsci12081098
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Bilateral Anodal tDCS over Left and Right DLPFC on Executive Functions in Children with ADHD

Abstract: Transcranial direct current stimulation (tDCS) is increasingly used for therapeutic purposes in attention-deficit hyperactivity disorder (ADHD). The dorsolateral prefrontal cortex (DLPFC) is the most targeted region of tDCS studies in ADHD. There is limited knowledge and mixed results about the relevance of left or right DLPFCs in ADHD’s cognitive deficits. No study so far has investigated the impact of the increased excitability of both left and right DLPFC with anodal tDCS on cognitive deficits in ADHD. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
(75 reference statements)
0
10
0
Order By: Relevance
“…Another experiment of this study did not report improvement in cognitive flexibility during anodal right cathodal left dlPFC stimulation and an reversed order electrode placement compared to sham condition 53 . A bilateral anodal dlPFC stimulation study showed no alteration of WCST measures during real, as compared to sham stimulation 36 . Given different stimulation modalities and target areas, we cannot make a clear conclusion about the role of the dlPFC and vmPFC in cognitive flexibility based on these studies.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Another experiment of this study did not report improvement in cognitive flexibility during anodal right cathodal left dlPFC stimulation and an reversed order electrode placement compared to sham condition 53 . A bilateral anodal dlPFC stimulation study showed no alteration of WCST measures during real, as compared to sham stimulation 36 . Given different stimulation modalities and target areas, we cannot make a clear conclusion about the role of the dlPFC and vmPFC in cognitive flexibility based on these studies.…”
Section: Discussionmentioning
confidence: 84%
“…In accordance, anodal left/cathodal right dlPFC stimulation improved working memory performance 33 , while anodal stimulation of the right dlPFC with an extracranial reference electrode improved inhibitory control in children with ADHD 35 . However, an online bilateral anodal left and right dlPFC stimulation protocol with extracranial reference electrodes did not improve working memory, inhibitory control and cognitive flexibility, as compared with sham stimulation in children with ADHD 36 . A face to face tES study in ADHD recently compared tDCS (anodal dlPFC/cathodal vmPFC stimulation) with tRNS (bilateral dlPFC stimulation) in ADHD, and found a larger tRNS effect on ADHD symptoms, and working memory performance 37 .…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…The stimulation time in the active group was 15 min, with a current intensity of 1.5 mA. Bilateral anodal left and right DLPFC tDCS did not enhance performance regarding inhibitory control, working memory, and cognitive flexibility ( 47 ).…”
Section: Discussionmentioning
confidence: 99%